Assessment of Primary Health Care Specialized Reference Clinics in Riyadh First Health Cluster: Outcome, Cost-Effectiveness and Patient Satisfaction - Alshowair A; Altamimi S; Alruhaimi F; Tolba A; Almeshari A; Almubrick R; Abdel-Azeem A (Dove Medical Press, 2022)
Abdulmajeed Alshowair,1 Saleh Altamimi,1 Faisal Alruhaimi,1 Ali Tolba,1 Alhanouf Almeshari,2 Rehab Almubrick,3 Amro Abdel-Azeem3,4 1Community Health Excellence, Riyadh First Health Cluster Ministry of Health, Riyadh, Saudi Arabia; 2Public Health Administration, Riyadh First Health Cluster Ministry of Health, Riyadh, Saudi Arabia; 3Population Health Management, Riyadh First Health Cluster Ministry of Health, Riyadh, Saudi Arabia; 4Department of Community, Environmental and Occupational Medicine, Faculty of Medicine Zagazig University, Zagazig, EgyptCorrespondence: Amro Abdel-Azeem, Population Health Management, Riyadh First Health Cluster Ministry of Health, Riyadh, Saudi Arabia, Tel +966 547135224, Email dr_amro_osh@hotmail.comPurpose: The objectives of the study are to assess the outcome and cost-effectiveness of specialized reference clinics (SRCs) in primary health care centers (PHCCs) of Riyadh First Health Cluster (RFHC), then to estimate the patient satisfaction among clients utilizing such SRCs.Patients and Methods: This facility-based study was conducted in Riyadh city, Saudi Arabia among six PHCCs in RFHC that contain SRCs. Records of all patients utilizing SRCs and their referral information were studied along two years. An in-depth interview was conducted with health care providers in SRCs. Cost analysis was calculated by the financial support group within RFHC. Also, a randomly selected 400 subjects utilizing SRCs were asked to fill patient satisfaction questionnaire.Results: Over two years, a total number of 55,084 patients utilized SRCs among different specialties. Most of these patients (86.7%) had full medical service within PHC-SRCs with no need for referral to hospitals. SRCs are significantly effective in decreasing the burden on hospitals in most specialties (p < 0.001). This effectiveness is significantly increased during the 2nd year of service. The time spent until appointment is significantly reduced from an average of six weeks in hospitals to an average of one week in SRCs. SRCs are very cost-effective as they reduced referrals to hospitals by 86.7% among 55,084 patients who utilized SRCs over two years, saving total costs of about 14.08 million Saudi Riyals (3.75 million US dollars). Most of the specialties are cost-effective except for urology and general surgery clinics, which are not cost-effective. Patient satisfaction is high regarding all service domains. The overall patient satisfaction score increased from 71.4% in the 1st year up to 73.2% in the second year.Conclusion: PHC-SRCs are cost-effective health services and their creation is reasonable and beneficial in terms of reducing costs of health care delivery, reducing the burden on hospitals, and improving patient satisfaction.Keywords: specialized reference clinics, outcome, cost-effectiveness, patient satisfaction, primary health care